Age‐related changes in murine myometrial transcript profile are mediated by exposure to the female sex hormones. Issue 1 (21st October 2015) - Chong, Hsu P.; Cordeaux, Yolande; Ranjan, Yorain Sri; Richardson, Sylvia; Liquet, Benoit; Smith, Gordon C. S.; Charnock‐Jones, David Stephen
Summary: In humans, the risk of operative first delivery increases linearly with maternal age. We previously hypothesized that prolonged, cyclical, prepregnancy exposure to estrogen and progesterone contributes to uterine aging. Here, we test this hypothesis. Myometrium was obtained from four groups of virgin mice: (i) 10‐ to 12‐week‐ and 28‐ to 30‐week‐old mice; (ii) 10‐ to 12‐week‐ and 38‐ to 40‐week‐old mice; (iii) 38‐week‐old mice that had an ovariectomy or sham operation early in life; (iv) 38‐week‐old mice that had been treated with progesterone or vehicle containing implants from 8 to 36 weeks. Transcript profiling was carried out using Affymetrix Gene ST 1.1 arrays, and data were normalized. We identified 60 differentially regulated transcripts associated with advancing age (group 1). We validated these changes in group 2 ( P for overlap = 5.8 × 10 −46 ). Early ovariectomy prevented the age‐related changes in myometrial transcript profile. Similarly, progesterone‐mediated long‐term ovarian suppression prevented the age‐related changes in myometrial transcript profile. Interferon regulatory factor 7 (Irf7) mRNA was regulated by age and hormonal exposure, and was identified as a predicted regulator of the other differentially expressed transcripts by both promoter sequence and canonical pathway activation analysis ( P = 8.47 × 10 −5 and P < 10 −10, respectively). Immunohistochemistry demonstrated IRF7 in both mouse and human myometrium. We conclude the following: (i) Myometrial aging in mice is associated with reproducible changes in transcript profile; (ii) these changes can be prevented by interventions which inhibit cyclical changes in the female sex hormones; and (iii) IRF7 may be an important regulator of myometrial function and aging.